Infinite Existence Solutions of Fractional Systems with Lipschitz Nonlinearity - Rafik Guefaifia; Salah Mahmoud Boulaaras; Bahri Cherif; Taha Radwan (Journal of Function Spaces)
The paper deals with the existence of infinitely many solutions of a class of perturbed nonlinear fractional p-Laplacian differential systems using one control parameter combined with the variational method.